The Principal’s Role in Implementing Excellent Service at Madrasah - Agus Sholeh; Ahmad Shofiyuddin Ichsan (Yayasan Zia Salsabila, 2025)
This study aims to analyse the role of the school principal in implementing excellent service at MTs N 8 Sleman by integrating the excellent service concept based on the A3 approach (Attitude, Attention, Action) and A6 principles (Attitude, Attention, Action, Competence, Appearance, Responsibility). A qualitative descriptive method was employed through observation, interviews, and documentation to illustrate how the principal enhances school community satisfaction and manages Islamic education. The results show that the principal demonstrates a friendly and professional attitude, sincerely attends to the needs of the school community, and takes swift, precise, and effective actions. These efforts have positively impacted the school's image and student learning motivation. Furthermore, the principal assumes full responsibility for maintaining a transparent and accountable excellent service. The implementation of excellent service rooted in A3 and A6 serves as an innovative managerial model, strengthening the Islamic education system in the modern era.